a) \(x + \left( { - \frac{2}{9}} \right) = \frac{{ - 7}}{{12}}\)
\(x = \frac{{ - 7}}{{12}} + \frac{2}{9}\)
\(x = \frac{{ - 21}}{{36}} + \frac{8}{{36}}\)
\(x = \frac{{ - 13}}{{36}}\)
Vậy \(x = \frac{{ - 13}}{{36}}\).
b) \(( - 0,1) - x = \frac{{ - 7}}{6}\)
\(\frac{{ - 1}}{{10}} - x = \frac{{ - 7}}{6}\)
\(x = \frac{{ - 1}}{{10}} + \frac{7}{6}\)
\(x = \frac{{ - 3}}{{30}} + \frac{{35}}{{30}}\)
\(x = \frac{{32}}{{30}}\)
\(x = \frac{{16}}{{15}}\)
Vậy \(x = \frac{{16}}{{15}}\)
c) \(( - 0,12) \cdot \left( {x - \frac{9}{{10}}} \right) = - 1,2\)
\(\frac{{ - 3}}{{25}} \cdot \left( {x - \frac{9}{{10}}} \right) = \frac{{ - 6}}{5}\)
\(x - \frac{9}{{10}} = \frac{{ - 6}}{5}:\left( {\frac{{ - 3}}{{25}}} \right)\)
\(x - \frac{9}{{10}} = \frac{{ - 6}}{5}.\frac{{ - 25}}{3}\)
\(x - \frac{9}{{10}} = 10\)
\(x = 10 + \frac{9}{{10}}\)
\(x = \frac{{109}}{{10}}\)
Vậy \(x = \frac{{109}}{{10}}\).
d) \(\left( {x - \frac{3}{5}} \right):\frac{{ - 1}}{3} = 0,4\)
\(\left( {x - \frac{3}{5}} \right):\frac{{ - 1}}{3} = \frac{2}{5}\)
\(x - \frac{3}{5} = \frac{2}{5}.\frac{{ - 1}}{3}\)
\(x - \frac{3}{5} = \frac{{ - 2}}{{15}}\)
\(x = \frac{{ - 2}}{{15}} + \frac{3}{5}\)
\(x= \frac{{ - 2}}{{15}} + \frac{9}{15}\)
\(x = \frac{7}{{15}}\)
Vậy \(x = \frac{7}{{15}}\).